Tuberous root production in "mauka" cultivar (Mirabilis expansa [Ruiz and Pavón] Standley) with application of organic fertilizer and chemical fertilization in Puno - Peru - Zapana Pari, Juan Gregorio (2017)
In the Puno region the population increases as the years go by, but food production does not follow the same direction, which leads, among other things, to problems of child malnutrition and, therefore, it is necessary to look for other alternatives to maintain the sovereignty and food sufficiency, considering that it is possible to improve the production of the "mauka" (Mirabilis expansa) crop, the present study was carried out with the objective of determining the tuberous root yield of the "mauka" when it is incorporated into the soil, cattle manure and urea plus triple calcium superphosphate. The treatments were: 7.5 t / ha of cattle manure (T1); 130 kg / ha of urea to 46% of N plus 90 kg / ha of triple calcium superphosphate to 46% of P2O5 (T2) and control (T3). Local plantation cuttings with 0.80 m spacing between furrows and 0.50 m between plants were used in loamy loam soil with 4 replications in Complete Batch Design. After one year of installation, a yield of 78.5 t/ha was obtained in treatment T2 (urea plus triple calcium superphosphate), followed by treatment T1 (beef manure) with 46.4 t/ha and finally the control T3 produced 31.6 t/ha. Additionally, the result shows that the plant reached 66.3 cm in height in treatment T2; 50.7 cm in treatment T1, and 39.6 cm in treatment T3, concluding that the effects were positive in relation to previous harvests and contributes to the sustainability of the production.